A social curiosity-driven approach to analyzing the information dissemination in Telegram political groups - Vasconcelos, Francisco F.; Sousa, Alexandre M. de; Almeida, Jussara M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Social curiosity plays a key role in the process of information dissemination on online social media platforms such as Telegram. Understanding the mechanisms that influence this process, especially in times of political unrest such as the Brazilian elections of 2022, is crucial. Recent studies have shown that curiosity is an important factor influencing user behavior when sharing information on online social media platforms. However, there are few studies that measure curiosity on these platforms, and none of them look at Telegram groups. The present study aims to fill this gap by investigating social curiosity in Telegram groups. The aim is to analyze how social curiosity affects user behavior, information sharing and understand the role of groups in stimulating social curiosity.